Pengembangan Media & Multimedia Pembelajaran Pendidikan Agama Islam - Khairunnida; Syahida Ajrina; Ani Cahyadi (Yayasan Al-Afif, 2026)
The development of digital media and interactive multimedia is necessary in the context of today's modern learning, including Islamic Religious Education learning which is not only oriented towards knowledge aspects, but also oriented towards the attitudes and skills of students, so as to be able to form a complete Muslim personality. This study aims to examine the development of learning media and multimedia that can be used in Islamic Religious Education learning activities. This study uses a qualitative approach with a type of library research through the review and analysis of various literature sources, such as books, journals, and relevant scientific articles. The results of the study indicate that the development of digital media and interactive multimedia in Islamic Religious Education learning must pay attention to important principles therein, including suitability with the curriculum, affordability, openness, independence, meaningfulness, sustainability, effectiveness and efficiency, as well as interactive and interesting. The development of technology-based media carried out systematically is part of a strategic step to create interactive, effective, interesting learning, and able to encourage active involvement of students in understanding and practicing Islamic values ​​in everyday life.